A Reusable MOF‐Supported Single‐Site Zinc(II) Catalyst for Efficient Intramolecular Hydroamination of o‐Alkynylanilines. (2nd May 2019) - Li, Beibei; Ju, Zhanfeng; Zhou, Mi; Su, Kongzhao; Yuan, Daqiang
Abstract: The exploitation of new and active earth‐abundant metal catalysts is critical for sustainable chemical production. Herein, we demonstrate the design of highly efficient, robust, and reusable Zn II ‐bipyridine‐based metal–organic framework (MOF) catalysts for the intramolecular hydroamination of o ‐alkynylanilines to indoles. Under similar conditions homogeneous catalytic systems mainly provide hydrolysate. Our results prove that MOFs support unique internal environments that can affect the direction of chemical reactions. The Zn II ‐catalyzed hydroamination reaction can be conducted without additional ligands, base, or acid, and is thus a very clean reaction system with regard to its environmental impact. Abstract : Innere Werte : Postsynthetische Funktionalisierung eines Zr‐basierten Metall‐organischen Gerüstes (MOF) mit einem Zn‐Salz ergibt einen edelmetallfreien, wiederverwendbaren und robusten Single‐Site‐Zn II ‐Katalysator mit herausragender Aktivität für die intramolekulare Hydroaminierung von o ‐Alkinylanilinen. Diese Ergebnisse lassen darauf schließen, dass ein MOF‐Träger eine einzigartige interne Umgebung liefern kann, die die Richtung von Reaktionen lenken kann.